Interpersonal relationships as coping mechanisms during bed rest: a thematic synthesis literature review - Cikač, Ana; Pišot, Saša (Frontiers in Psychology, 2025)
Bed rest (BR) studies are primarily designed to investigate the effects of weightlessness on the human body, but they are also used to study the effects of physical inactivity. For this purpose, participants are typically recruited from the general population without requiring specialized training, which contrasts with the selection process for cosmonauts. The BR study environment is often characterized as highly stressful, highlighting the importance of understanding coping mechanisms and adaptation strategies among participants, as well as the role of their daily interactions. This review aims to determine whether interpersonal relationships and the concept of social connectedness (SC) have been explored within the context of BR studies. For the search strategy, the definition of exclusion criteria, and the initial screening, PRISMA 2020 statement was followed. The PEO framework was used to generate keywords, and thematic synthesis was applied for data extraction, analysis, and synthesis. An initial search did not uncover any studies examining the concept of SC in the context of BR as an environment with extreme conditions, suggesting that SC in this context has not yet been investigated. While findings of thematic synthesis indicate that interpersonal relationships play a significant role in coping with and adapting to the extreme conditions of BR studies. As results showed these relationships can have both positive and negative effects. Interpersonal relationships also serve as a crucial support mechanism among participants. Additionally, how participants make sense of their involvement in such studies remains underexplored, and further research in this area is recommended in the discussion.